2022
DOI: 10.1038/s41598-022-23844-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptome analysis of the orphan crop tef (Eragrostis tef (Zucc.) Trotter) under long-term low calcium stress

Abstract: Calcium (Ca2+) is one of the essential mineral nutrients for plant growth and development. However, the effects of long-term Ca2+ deficiency in orphan crops such as Tef [(Eragrostis tef) (Zucc.) Trotter], which accumulate high levels of Ca in the grains, remained unknown. Tef is a staple crop for nearly 70 million people in East Africa, particularly in Ethiopia and Eritrea. It is one of the most nutrient-dense grains, and is also more resistant to marginal soils and climatic conditions than main cereals like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…As a nutrient element essential for plant growth and development, calcium is involved in a variety of cellular metabolic processes [92]. Ligaba-Osena et al [93] showed that under low calcium concentrations, GO analysis highlighted the significant enrichment of several Ca 2+ transporters, signaling genes, genes with transport activities, ATPase activity, catalytic activities, etc. Wang et al [84] found that the application of exogenous calcium increased the proline and soluble sugar content in tea (Camellia sinensis) and improved heat resistance by enhancing heat stress signal transduction to mitogen-activated protein kinase terms.…”
Section: The Nitrogen-calcium Ratio Regulates Different Plant Growth ...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a nutrient element essential for plant growth and development, calcium is involved in a variety of cellular metabolic processes [92]. Ligaba-Osena et al [93] showed that under low calcium concentrations, GO analysis highlighted the significant enrichment of several Ca 2+ transporters, signaling genes, genes with transport activities, ATPase activity, catalytic activities, etc. Wang et al [84] found that the application of exogenous calcium increased the proline and soluble sugar content in tea (Camellia sinensis) and improved heat resistance by enhancing heat stress signal transduction to mitogen-activated protein kinase terms.…”
Section: The Nitrogen-calcium Ratio Regulates Different Plant Growth ...mentioning
confidence: 99%
“…In studies on perennial ryegrass, KEGG enrichment analysis indicated that "photosynthesis-antenna protein" may have a positive response to appropriate nitrogen conditions, while "steroid biosynthesis", "carotenoid biosynthesis", and "c5 bis metabolism" are the most significantly enriched pathways in response to excess nitrogen [99]. Meanwhile, Ca 2+ deficiency affects plant growth and mineral accumulation by regulating the transcription of Ca 2+ transporter, Ca 2+ -binding protein, and Ca 2+ -dependent protein kinase and signaling genes [93]. Photosynthetic metabolism is one of the most enriched KEGG pathways in plants under high calcium stress.…”
Section: Nitrogen-calcium Synergies Activate Metabolic Pathways Relat...mentioning
confidence: 99%
“…Compared to other major cereals such as wheat, rice, barley, oats, maize, tef grains are high in amino acid, protein, fiber, vitamin, and mineral content (Zhu 2018 ; Girija et al 2022b ). Tef grains are also gluten free with low glycemic index which makes it an alternative cereal for people suffering from gluten intolerance and Type 2 diabetes (Ligaba-Osena et al 2020 , 2022 ). As a result, apart from Ethiopia, tef is cultivated as a food and forage crop in USA, Netherlands, South Africa, Australia, Indian, Kenya and Israel (Tadele and Hibistu 2021 ).…”
Section: Introductionmentioning
confidence: 99%